2019
DOI: 10.3389/fmicb.2019.01357
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Human Antimicrobial RNase Chimera Against Bacterial Resistance

Abstract: The emergence of bacterial resistance to the most commonly used antibiotics encourages the design of novel antimicrobial drugs. Antimicrobial proteins and peptides (AMPs) are the key players in host innate immunity. They exert a rapid and multifaceted action that reduces the development of bacterial adaptation mechanisms. Human antimicrobial RNases belonging to the vertebrate specific RNase A superfamily participate in the maintenance of tissue and body fluid sterility. Among the eight human canonical RNases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…Of initial concern for this study was the potential cytotoxicity of RNases [ 61 ]. However, recent studies demonstrated that the modified RNase 3/1 protein showed low cytotoxicity for concentrations up to 200 μM [ 15 ]. Cytotoxicity assays were conducted for two model cell lines, i.e., THP-1 and Vero.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of initial concern for this study was the potential cytotoxicity of RNases [ 61 ]. However, recent studies demonstrated that the modified RNase 3/1 protein showed low cytotoxicity for concentrations up to 200 μM [ 15 ]. Cytotoxicity assays were conducted for two model cell lines, i.e., THP-1 and Vero.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, there is an urgent need to develop more effective treatments to avoid the intracellular growth of pathogenic microorganisms. Previously, our research group designed and explored the mechanism of action of a novel hybrid ribonuclease RNase 3/1, towards Gram-negative microorganisms [15]. Additionally, numerous studies have demonstrated the effective activity of the human RNase 3 to inhibit the intracellular growth of several microorganisms, including Mycobacterium [16] and even the proliferation of biofilm structures of P. aeruginosa [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations